Exploring Hyponyms: Taxonomic Structure and Semantic Features (Texas Journal of Philology, Culture and History, 2024)
The article examines the concept of hyponyms, focusing on their taxonomic structure and semantic features. It delves into the hierarchical relationship between hyponyms and hypernyms, exploring how specific terms are classified under broader categories. Additionally, it investigates the distinguishing characteristics and properties that differentiate hyponyms within specific domains, providing insights into their organization and semantic differentiation based on taxonomic structure.